Apresentação da Seção Temática - Educação e Mundos Imagéticos e Sonoros - Nilda Alves; Carlos Eduardo Ferraço; Alessandra Nunes Caldas (Universidade Federal do Rio Grande do Sul, 2017)
Apresentação da Seção Temática - Educação e Mundos Imagéticos e Sonoros.